Development Barriers of PE/VC Sector in Poland - Jabłoński, Sebastian; Waszkiewicz, Maciej (Bariery rozwoju sektora PE/VC w Polsce, 2009)
In the following article the authors comprised their remarks and conclusions flowing out from the observation of the market and their own research concerning Private Equity/Venture Capital funds. Further more it has been tried to determine the most important barriers slowing the dynamics of this sector in Poland and assembling a model of the environment that is favorable to the further development. This is especially true for small and medium size ventures including entrepreneurs. The global expansion of the capital market has deployed a large access to the capital to start innovative projects. In Poland there are plenty of ideas to realize the commercial projects. The question is posed as to what is ratio between the massive of the capital versus number of viable projects? Do the ventures that implement the innovative projects have access to the capital? Do the VC funds have their own developed strategy tailored to the market conditions and project requirements? And how they are willing to take risk and park their capital in these undertakings? These aforementioned questions are being analyzed by the authors. (fragment of text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 48, s. 338-346